Associations between two conceptualizations of materialism and subjective wellbeing in China: A meta-analysis of studies from 1998 to 2022 - Zhou, Kaiji; Lu, Lin; Hu, Liqun; Wang, Yingzhao (Frontiers in Psychology, 2022)
This meta-analysis examines the relationship between materialism (materialistic values and extrinsic aspirations) and subjective well-being in the Chinese population. Fifty-six relevant studies covering the period from 1998 to 2022 were included in the meta-analysis. Fifty-eight independent effect sizes from a total of 52,368 participants were obtained to calculate the mean effect sizes. Materialistic values correlated with significantly lower subjective well-being (r = −0.205), while the mean effect size for extrinsic aspirations was found to be not significant (r = −0.048). The effect sizes varied across different types of well-being outcomes (materialistic values: rs = −0.095 to −0.202; extrinsic aspirations: rs = 0.066 to −0.125). The associations were also moderated by certain demographic factors (age and gender), methodological factors (study design and scoring method), publication features (type of publication and publication year), and economic indicators (economic growth and wealth inequality). We discuss our limitations and the implications for future research.